2004
DOI: 10.4321/s1130-01082004000700004
|View full text |Cite
|
Sign up to set email alerts
|

The journal impact factor as a parameter for the evaluation of researchers and research

Abstract: The journal impact factor (IF), which is published annually by the Institute for Scientific Information ® (USA), is meanwhile in widespread use as a scientometric parameter for the evaluation of research and researchers in Germany and other European countries. The present article subjects the IF to critical analysis. It first deals with processes of production, transfer, and use of medical knowledge, because the IF intervenes in these processes on account of its reflexivity. Secondary effects of the IF resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 88 publications
0
41
0
Order By: Relevance
“…[9][10][11][12][13][14] Certainly, the actual impact on the community of an article is not necessarily related to the IF. …”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Certainly, the actual impact on the community of an article is not necessarily related to the IF. …”
Section: Discussionmentioning
confidence: 99%
“…Surveying physicians to rate the quality of journals, the validity of the impact factor as an indicator of quality for General Medicine was examined and revealed that it may be a credible measure (Saha, Saint, & Christakis, 2003). But, as many studies have confirmed, it cannot be a reasonable indicator of quality for an individual article (Seglen, 1997a;1997b;1997c;Garfield, 1998;Whitehouse, 2001;Kaltenborn & Kuhn, 2004;Gracza & Somoskovi, 2007). Campbell (2008) declares that the journal impact factor is suitable to measure impact at national and institutional levels but not at the individual level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has led to considerable controversy [5][6][7][8][9][10][11][12][13][14][15][16] and some ethical concerns, 17-22 along with fueling a search for better numeric measures of academic quality [23][24][25][26][27] (of course, the ultimate method to evaluate quality would be the careful examination of research publications; unfortunately, reading seems too cumbersome for administrators seeking only numbers for ranking).…”
Section: Anne-wil Harzingmentioning
confidence: 99%